Promoting inclusive facilitation of participatory agricultural research for development. Issue 1 (2nd January 2023) - Dey de Pryck, Jennie; Elias, Marlène
ABSTRACT: Participatory research is widely practised in agricultural research for development (AR4D). Yet, it is often applied technocratically by facilitators who are ill-prepared to engage with the unequal power relations that embed AR4D. We contend that participatory research has the potential to foster inclusive spaces for local identification of development challenges and solutions but that this requires a skilled and self-reflective facilitation of participatory processes. Several strategies can enhance the meaningful participation of women and marginalised groups in participatory research. Understanding these strategies and how to implement these thoughtfully should be integral to a facilitator's preparation and training.